Preparation of Mesoporous Basic Oxides through Assembly of Monodispersed Mg–Al Layered Double Hydroxide Nanoparticles. Issue 39 (22nd June 2017) - Oka, Yuya; Kuroda, Yoshiyuki; Matsuno, Takamichi; Kamata, Keigo; Wada, Hiroaki; Shimojima, Atsushi; Kuroda, Kazuyuki
Abstract: Mesoporous basic Mg–Al mixed metal oxides (MMOs) with a high surface area and large pore size have been prepared through the assembly of monodispersed layered double hydroxide nanoparticles (LDHNPs) with block copolymer templates. The particle sizes of the LDHNPs were mainly controlled by varying the concentration of tris(hydroxymethyl)aminomethane (THAM), which was used as a surface stabilizing agent. LDHNPs and micelles of a block copolymer (Pluronic F127) were assembled to form a composite. The composites were calcined to transform them into mesoporous MMOs and to remove the templates. The Brunauer–Emmett–Teller surface areas, mesopore sizes, and pore volumes increased as a result of using the templates. Moreover, the pore sizes of the mesoporous MMOs could be controlled by using LDHNPs of different sizes. The mesoporous MMOs prepared from the LDHNPs showed much higher catalytic activity than a conventional MMO catalyst for the Knövenagel condensation of ethyl cyanoacetate with benzaldehyde. The mesoporous MMO catalyst prepared using the smallest LDHNPs, about 12 nm in size, showed the highest activity. Therefore, the use of monodispersed LDHNPs and templates is effective for preparing highly active mesoporous solid base catalysts. Abstract : Controlled mesopore formation : Mesoporous Mg–Al mixed metal oxides (MMOs) with the highest surface area (ca. 400 m 2 g −1 ) among reported MMOs have been prepared through the assembly of finely controlled layered double hydroxide nanoparticles and a block copolymer micelle followed by calcination (see graphic). The mesoporous MMOs showed very high catalytic activity for the Knövenagel condensation.